2009
DOI: 10.1111/j.1365-2672.2009.04305.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus niger var. taxi, a new species variant of taxol-producing fungus isolated from Taxus cuspidata in China

Abstract: Aims:  To characterize and identify a new taxol‐producing fungal strain HD86‐9 isolated from Taxus cuspidata in China. Methods and Results:  Taxol extracted from strain HD86‐9 was identified by HPLC and MS analyses. Strain HD86‐9 was cultured and its morphology and phenotypes were described. HD86‐9 displayed morphology most similar to that of Aspergillus niger but presented differences in the shape and size of the conidia. The growth evaluation showed that the maximal tolerable temperature of the new strain wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 7 publications
3
46
0
Order By: Relevance
“…Several other groups soon confirmed the findings in this ground-breaking publication and provided additional supporting evidence (Flores-Bustamante et al 2010). Microbial Taxol and taxane biosynthesis was found in several different genera of fungi, including Alternaria, Aspergillus, Cladosporium, Fusarium, Monochaetia, Pestlotia, Pestalotiopsis, Pithomyces, Penicillium and Xylaria, which were isolated from yew and non-Taxus plants (FloresBustamante et al 2010;Strobel et al 1996;Soca-Chafre et al 2011;Zhang et al 2009;Zhao et al 2009;Hoffman 2003). Recently, several reports have been published claiming that endophytic fungi contain genes previously identified in Taxus spp.…”
Section: Introductionsupporting
confidence: 55%
“…Several other groups soon confirmed the findings in this ground-breaking publication and provided additional supporting evidence (Flores-Bustamante et al 2010). Microbial Taxol and taxane biosynthesis was found in several different genera of fungi, including Alternaria, Aspergillus, Cladosporium, Fusarium, Monochaetia, Pestlotia, Pestalotiopsis, Pithomyces, Penicillium and Xylaria, which were isolated from yew and non-Taxus plants (FloresBustamante et al 2010;Strobel et al 1996;Soca-Chafre et al 2011;Zhang et al 2009;Zhao et al 2009;Hoffman 2003). Recently, several reports have been published claiming that endophytic fungi contain genes previously identified in Taxus spp.…”
Section: Introductionsupporting
confidence: 55%
“…have been found in many medicinal plants, including Taxus cuspidate (Zhao et al, 2009), Cephalotaxus mannii (Xue et al, 2012), Melia azedarach . Many antimicrobial compounds had been isolated and characterized from these endophytic fungi, such as diterpenoids (Sun et al, 2012), alkaloids (Zhan et al, 2007;Ding et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies have reported the screening of paclitaxel-producing fungi using the biosynthetic genes as molecular markers. 27,[29][30][31][32]58,59 A first partial fungal TS-coding sequence (ts) was reported for M. rouxianus, a fungus isolated from T. chinensis. 28 The sequence (632 bp) showed 98% identity to that of T. brevifolia (U48796).…”
Section: Genes Of the Paclitaxel Biosynthetic Pathwaymentioning
confidence: 99%